2007
DOI: 10.1080/01919510701463206
|View full text |Cite
|
Sign up to set email alerts
|

The Return of Ozone and the Hydroxyl Radical to Wastewater Disinfection

Abstract: The City of Phoenix, Arizona is investigating various disinfection technologies for its 91st Avenue wastewater treatment facility: (1) ultraviolet light (UV), (2) ozone, (3) UV/hydrogen peroxide, (4) ozone/hydrogen peroxide, (5) and UV/ozone. In addition to providing disinfection, the City would like to consider the removal of endocrine disrupting chemicals (EDCs) and personal and pharmaceutical care products (PPCPs) in the treatment technology evaluation. To identify the most economical disinfection system, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…9 A majority of nitrosamine research has focused on its formation from chloramination. Given its efficacy in oxidizing a wide variety of trace organic contaminants [16][17][18][19] and inactivating disinfectantresistant microorganisms, [20][21][22][23][24] ozone is becoming increasingly popular in water reuse applications. [10][11][12][13][14][15] Nitrosamine formation during ozonation is generally limited to NDMA at relatively low concentrations (<25 ng L −1 ), but there are water matrices in which NDMA formation can exceed 100 ng L −1 .…”
Section: Introductionmentioning
confidence: 99%
“…9 A majority of nitrosamine research has focused on its formation from chloramination. Given its efficacy in oxidizing a wide variety of trace organic contaminants [16][17][18][19] and inactivating disinfectantresistant microorganisms, [20][21][22][23][24] ozone is becoming increasingly popular in water reuse applications. [10][11][12][13][14][15] Nitrosamine formation during ozonation is generally limited to NDMA at relatively low concentrations (<25 ng L −1 ), but there are water matrices in which NDMA formation can exceed 100 ng L −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies specifically addressing the efficacy of ozone for TOrC elimination, reductions in estrogenicity, and the effects on toxicity have also been performed in pilot-and full-scale systems (Huber et al, 2005;Hollender et al, 2009;Wert et al, 2009a;Stalter et al, 2010aStalter et al, , 2010bGerrity et al, 2011a;Gerrity and Snyder, 2011;Zimmermann et al, 2011). Ozone is also effective for the inactivation of a wide range of microbial indicators and pathogens (Driedger et al, 2001;Burns et al, 2007;Gerrity et al, 2011a). This demonstrated efficacy for TOrC mitigation and disinfection has established ozone as a viable option for wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al (2002) suggested that the transferred ozone dose is the critical parameter in ozonation of wastewater compared with the Ct values for natural waters. Burns et al (2007) reported on ozone doses required for virus inactivation in wastewater, where an applied ozone dose of 3, 5, and 8 mg/L resulted in an ozone concentration after 30 s of < 0.1, 0.6, and 2.5 mg/L, respectively. They concluded that a 5 mg/L transferred ozone dose (equivalent to a Ct = 0.5 (mg/L)-min) was capable of achieving a 6-log virus inactivation credit.…”
Section: Inactivation Of Pathogenic Viruses By Ozonementioning
confidence: 99%
“…Numerous studies have exhibited the complexities of determining a clear ozone CT value in wastewaters for reporting dose response of microorganisms (e.g., Xu et al, 2002;Tanner et al, 2004;Burns et al, 2007;Ishida et al, 2008), thus many of these results are not universally transferrable to other studies. To determine the effect of ozone demand by wastewater, we compared the inactivation of E. coli in PBS and wastewater in Figure 5.…”
Section: Ozone Inactivation Of Surrogates and Pathogenic Viruses In Wmentioning
confidence: 99%